KEKUATAN MENGINGKAT KLAUSULA SYARAT BATAL DALAM KONTRAK BISNIS YANG MENYAMPINGKAN KETENTUAN PASAL 1266 DAN PASAL 1267 KUH PERDATA - Christopher Iskandar; Ningrum Natasya Sirait; Runtung Runtung; Mahmul Siregar (Universitas Sumatera Utara, 2014)
ABSTRACT The termination clause in business contracts that overrules the Article (s) 1266 and 1267 of the Civil Code serves to protect the creditors on one side but on the other side is detrimental to the debtors when they fail to carry out the performance. Some of the problems formulations in this thesis are how the binding strength of the termination clause that overrules the Article (s) 1266 and 1267 in business contracts and how the impelementations of the executions are to the business contracts with the termination clauses that overrule the Article (s) 1266 and 1267 of the Civil Code. The parties must be consistent with the agreement to overrule the Article (s)1266 and 1267 of the Civil Code so that the termination clause is binding. Futhermore, exceptio non adimpleti contractus and bad faith are some factors that cause the termination clause that overrules the Article (s) 1266 and 1267 of the Civil Code to not be binding. Finally, the implementations of parate executie should refer to The Verdict of Constitutional Court No. 70/PUU-VIII/2010 that strengthens the position of parate executie as fulfillment of performance for creditors to sell the mortgage objects without the fiat (order).